Burocrazia e università nel neoliberalismo - Zani, Gian Vito (Filosofia, 2017)
The present article examines the situation of Italian universities through the analysis of recent studies denouncing the business mentality and the increase of bureaucracy that characterize them. The business mentality is the result of the dominant neo-liberal thought analyzed by Michel Foucault in the course he taught at Collège de France in the years 1978-1979. This paper attempts to assess the role of bureaucracy in the different neo-liberal schools of thought by investigating Ludwig von Mises, Herbert A. Simon, and Gary Becker’s works. These analyses lead to the conclusion that, in mature neo-liberalism, bureaucracy is never in op- position to power and markets, as everything is subjected to the law of efficiency, thereby fulfilling Max Weber’s prediction of bureaucracy as a cage. Consequently, in order to defend themeselves from the single-minded logic of the market, Uni- versities have to promote disinterested research.